2017
DOI: 10.1186/s40560-017-0264-6
|View full text |Cite
|
Sign up to set email alerts
|

Time to re-think the use of dobutamine in sepsis

Abstract: Dobutamine is commonly used worldwide and included in the protocol for early goal-directed therapy (EGDT). Since the use of dobutamine in EGDT was reported, it has been considered to be an important component, especially in the treatment of septic patients with myocardial dysfunction. However, it is questionable whether dobutamine improves the mortality of sepsis and septic shock.In three recent randomized controlled trials (ProCESS, ProMISe, and ARISE trials), the frequency of dobutamine use was significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Current guidelines recommend the use of dobutamine for further ionotropic support (Grade 1C), but recent studies question its benefit [5,7]. Although dobutamine increases the cardiac index, it has not been shown to reduce mortality even in cases with severe heart failure (Ejection fraction <35%) [8]. One 2013 study suggested that it may even be associated with an increase in 90-day mortality [9].…”
Section: Discussionmentioning
confidence: 99%
“…Current guidelines recommend the use of dobutamine for further ionotropic support (Grade 1C), but recent studies question its benefit [5,7]. Although dobutamine increases the cardiac index, it has not been shown to reduce mortality even in cases with severe heart failure (Ejection fraction <35%) [8]. One 2013 study suggested that it may even be associated with an increase in 90-day mortality [9].…”
Section: Discussionmentioning
confidence: 99%
“…However, dobutamine increases cardiac output and splanchnic blood flow. In addition, dobutamine has not demonstrated a benefit in mortality and could even decrease survival [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the use of beta-blockers in septic shock has been linked to an increase in survival rate in some studies. 10 …”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the use of beta-blockers in septic shock has been linked to an increase in survival rate in some studies. 10 The use of levosimendan in cardiogenic shock during sepsis was first described in a 2005 case report. 11 Since then there have been small studies and other case reports that have shown better outcomes in terms of right and left ventricular contractility, ventricular coupling, cardiopulmonary performance, global oxygen and splanchnic perfusion when compared with dobutamine and placebo.…”
mentioning
confidence: 99%